Zooxanthellae Diversity and Coral-Symbiont Associations in the Philippine Archipelago: Specificity and Adaptability Across Thermal Gradients - Torres, Andrew F.; Valino, Darryl Anthony M.; Ravago-Gotanco, Rachel (Frontiers in Marine Science, 2021)
Prolonged thermal stress and high levels of solar irradiance can disrupt the coral-algal symbiosis and cause bleaching and lowered overall fitness that lead to the likely death of the cnidarian host. Adaptive bleaching and acclimatization of corals, which posits bleaching as an opportunity for the coral host to switch its currently susceptible endosymbionts to more stress-tolerant taxa, offers hope for survival of reefs amid rapidly warming oceans. In this study, we explored the diversity and distribution of coral-zooxanthellae associations in the context of geospatial patterns of sea surface temperature (SST) and thermal anomalies across the Philippine archipelago. Thermal clusters based on annual sea surface temperature means and each site’s frequency of exposure to heat stress were described using three-decade (1985–2018) remotely sensed data. Haphazard sampling of 628 coral fragments was conducted in 14 reef sites over 3 years (2015–2018). Using polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) fingerprinting and sequencing of the zooxanthellae ITS2 region, we characterized endosymbiont diversity within four reef-building coral families across archipelagic thermal regimes. Consistency in dominant Symbiodiniaceae taxon was observed in Acropora spp., Porites spp., and Heliopora coerulea. In contrast, the family Pocilloporidae (Pocillopora spp., Seriatopora spp., and Stylophora pistillata) exhibited biogeographic variability in zooxanthellae composition, concordant with inferred occurrences of sustained thermal stress. Multivariate analyses identify two broad Pocilloporidae clusters that correspond with mean SST ranges and frequency of exposure to bleaching-level thermal stress which are largely supported by ANOSIM. Differences in zooxanthellae assemblages may reflect host-specific responses to ecological or environmental gradients across biogeographic regions. Such patterns of variability provide insight and support for the adaptability and potential resilience of coral communities in geographically and oceanographically complex regions, especially amidst the increasing severity of global and local-scale stressors.